청미천에서 제방에 의해 격리된 옛홍수터의 경계 설정과 토지이용 분석 - 진승남(Seung-Nam Jin); 조강현(Kang-Hyun Cho); 조형진(Hyung-Jin Cho) (Ecology and Resilient Infrastructure, 2017)
For the restoration of lateral connectivity between channel and floodplain, it is important to find the former floodplain and to characterize its land use in streams which were channelized by the levee construction for the flood protection. The aim of this study is to map the former floodplains and to assess its land use pattern in the Cheongmi-cheon Stream, Korea. The former floodplains were explored by being overlapped on a digital elevation model (DEM), digital topographic map and design flood level using a geographical information system (GIS) in the Cheongmi-cheon Stream basin. The land use of the identified former floodplains was classified by land-use map. The total number of the former floodplains was 104 and their total area was $11.9km^2$ in the Cheongmi-cheon Stream. The land use pattern of the former floodplains was mostly farmland (87.1%). The former floodplains were usually surrounded by mountain forest in the downstream of the Cheongmi-cheon Stream. These former floodplains are probably suitable for restoration of lateral connectivity because of lower ratio of urban area but higher ratio of farmland. The results of delineation and land use analysis of the former floodplain can be used as a baseline data for planning stream restoration in the Cheongmi-cheon Stream. 우리나라의 하천은 대부분 치수를 위한 제방공사를 통해 직강화되어 있다. 하천과 홍수터의 횡적 연결성을 회복하기 위해서는 제방에 의해 격리된 옛홍수터를 탐색하고 현재 토지이용현황을 파악하는 것이 중요하다. 본 연구의 목적은 청미천에서 옛홍수터를 탐색하고 토지이용현황을 분석하는 것이다. 옛홍수터는 지리정보시스템을 이용하여 청미천 유역에서 수치표고모델, 연속수치지도 및 계획홍수위를 중첩하여 산출하였다. 탐색된 옛홍수터의 토지이용현황은 토지피복도를 이용하여 분류하였다. 청미천에서 격리된 옛홍수터는 총 104 지점이 탐색되었으며, 전체면적은 11.9 km2이었다. 옛홍수터의 토지이용은 농경지가 87.1%로 대부분을 차지하였다. 청미천의 하류에는 산지로 둘러싸인 소규모 패치 형태의 옛홍수터가 많았으며, 이러한 지역은 시가화지역의 비율이 낮고, 농경지의 비율이 높아 하천 횡적 연결성 복원의 효율이 높을 것이다. 청미천에서 탐색된 격리된 옛홍수터와 토지이용 현황은 향후 하천 복원계획에 기초자료로 이용될 수 있을 것이다.